Gestão das inovações tecnológicas na agroindústria do amendoim do estado de São Paulo - Depieri, Heitor Augusto (Universidade Federal de São Carlos, 2019)
Peanut is one of the foods that are already part of the Brazilian culture. The national consumption ranges from roasted, salted fruit to sweets (like the traditional paçoca) and derivatives containing peanut in their composition. The state of São Paulo is the largest producer and processor of this product. The main peanut-producing areas are the regions of Alta Paulista (Tupã and Marília) and Alta Mogiana (Dumont, Jaboticabal, Ribeirão Preto, and Sertãozinho). However, many opportunities are lost when it comes to adding value to this product, as 80% of the whole production of the state are shipped to other countries in the form of grains and the remaining is intended to supply the national sweets industry. Since the increased Dollar rate provides good financial results, the processed products are left out to export countries. Therefore, this dissertation aims at verifying how São Paulo-based companies are managing technological innovations in processing of peanut and implementing such technologies in order to increase competitiveness. To achieve that, a case study is to be carried out with the processors from the regions of Alta Paulista and Alta Mogiana. Interviews will be conducted with the support of a semi-structured questionnaire. An analysis of the patents filed involving the subject matter of this study will also be performed to verify in which fields there are innovations (regarding product and process) at the national and international levels. The finding results shows that the raw material originated from the processing companies have a strong influence by the industries who buy these materials, regarding the deciding process whether to innovate or not. And the food industries that are responsible for product from peanuts, are constantly interested and search for technology to guarantee the market demands and stay in it
Management of technological innovations in the agroindustries of peanut at the state of São Paulo
Keywords: Amendoim; Inovação tecnológica; Processamento; Competitividade; Peanut; Technological innovations; Processing; Competitiveness; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO